2015
DOI: 10.1097/mcg.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Does an Upper Endoscopy Before Transesophageal Echocardiography Change Patient Management?

Abstract: Our results demonstrate that an EGD before TEE can elucidate findings that may preclude the passage of a blind probe in patients with upper GI symptoms or known esophageal disease. Therefore, we propose that an EGD is clinically beneficial before TEE and can change patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…We hypothesize it may be of utility to hold anticoagulation until the esophagus is intubated to minimize risk for significant hemorrhage in the context of full‐dose anticoagulation. Additionally, a previous study has suggested use of upper endoscopy prior to TEE in certain high‐risk patients in an attempt to identify potential lesions and avoid a significant complication involving UGIB related to local trauma . This is an interesting consideration although this study's authors feel that the incidence of esophageal rings or similar high‐risk lesions are likely not prevalent enough to warrant preoperative upper endoscopy as a standard of care for TAVR patients.…”
Section: Discussionmentioning
confidence: 94%
“…We hypothesize it may be of utility to hold anticoagulation until the esophagus is intubated to minimize risk for significant hemorrhage in the context of full‐dose anticoagulation. Additionally, a previous study has suggested use of upper endoscopy prior to TEE in certain high‐risk patients in an attempt to identify potential lesions and avoid a significant complication involving UGIB related to local trauma . This is an interesting consideration although this study's authors feel that the incidence of esophageal rings or similar high‐risk lesions are likely not prevalent enough to warrant preoperative upper endoscopy as a standard of care for TAVR patients.…”
Section: Discussionmentioning
confidence: 94%
“…Although the presence of a pre-existing symptomatic hiatal hernia or pharyngeal pouch are both recognised as potential risk factors for oesophageal perforation, the practice guidelines for TOE utilisation indicate that there is disagreement amongst members and consultants as to whether these conditions should be viewed as an absolute contra-indication to TOE use ( 15 ). Upper gastrointestinal endoscopy may be considered for patients with known risk factors (like previous oesophageal surgery) to identify features that may preclude a subsequent TOE examination, for example the presence of a residual stricture/narrowing as these may alter management ( 28 ).…”
Section: Complications Associated With Toementioning
confidence: 99%
“…Several retrospective studies have found a complication rate of 0.2% to 1.4% after intraoperative TEE in cardiac surgery patients. 5,[10][11][12][13] These studies list an overall rate of complications discovered postoperatively that can be attributed to TEE but do not specify whether probe placement was difficult or required multiple attempts. Whether related to difficult placement or not, the low incidence of complications does confirm the overall safety of intraoperative TEE.…”
Section: Complications/contraindicationsmentioning
confidence: 99%
“…9 Most of the contraindications for TEE placement are related to either bleeding concerns or anatomical changes to the GI tract that would make insertion more difficult or more likely to result in a complication. Structural abnormalities associated with challenging placement of a TEE probe include extrinsic compression of the esophagus, gastritis, tortuous distal esophagus, retained food in the esophagus, gastric ulcer, esophageal erosion, 13 esophageal stricture, 14 esophageal fistula, esophageal atresia, 4 hypopharyngeal diverticula, 15 cardiomegaly, 16 fibrosis after radiation, and hiatal hernia. 17 Additionally, anecdotal reports have found difficult tracheal intubation to be a predictor of difficult esophageal intubation; therefore, some experts advocate placement of TEE probes under direct visualization in this situation.…”
Section: Complications/contraindicationsmentioning
confidence: 99%